2016
DOI: 10.1016/j.bbamem.2015.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the accumulation of P-glycoprotein substrates within cells: The effect of cholesterol on membrane partitioning

Abstract: The apparent activity of the multidrug transporter P-glycoprotein (P-gp) is enhanced by the presence of cholesterol. Whether this is due to the direct effect of cholesterol on the activity of P-gp, its effect on the local concentration of substrate in the membrane, or its effect on the rate of entry of the drug into the cell, is unknown. In this study, molecular dynamics simulation techniques coupled with potential of mean force calculations have been used to investigate the role of cholesterol in the movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…They showed that ibuprofen slightly enhanced the order of DMPC lipids, whereas in the presence of 50 mol% cholesterol, the opposite effect was observed [28]. The presence of cholesterol also affects the activity of efflux pumps, such as P-glycoprotein [26]. For instance, Subramanian et al (2016) evaluated the free energy profiles of several drugs within POPC lipid bilayers [26].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 4 more Smart Citations
“…They showed that ibuprofen slightly enhanced the order of DMPC lipids, whereas in the presence of 50 mol% cholesterol, the opposite effect was observed [28]. The presence of cholesterol also affects the activity of efflux pumps, such as P-glycoprotein [26]. For instance, Subramanian et al (2016) evaluated the free energy profiles of several drugs within POPC lipid bilayers [26].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…For instance, Subramanian et al (2016) evaluated the free energy profiles of several drugs within POPC lipid bilayers [26]. In the case of doxorubicin and nifedipine, cholesterol reduced their free energy in the centre of the bilayer [26]. Thus, it increased their local concentration in the membrane and, consequently, enhanced P-glycoprotein's ability to expel these drugs [26].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 3 more Smart Citations